Silver-coated monolithic columns for separation in radiopharmaceutical applications - Sedlacek, Ondrej; Kucka, Jan; Svec, Frantisek; Hruby, Martin (Journal of separation science, 2014)
In this study, we demonstrate the preparation of a macroporous monolithic column containing anchored silver nanoparticles and its use for the elimination of excess radioiodine from the radiolabeled pharmaceutical. The poly(glycidyl methacrylate-co-ethylene dimethacrylate) monolith was first functionalized with cystamine and the free thiol groups liberated by reaction with borohydride. In-house-prepared silver nanoparticles were then attached by interaction with the surface thiols. The deiodization process was demonstrated with the commonly used radiopharmaceutical m-iodobenzylguanidine labeled with radionuclide iodine-125.
Keywords: kovové nanočástice; 3-Iodobenzylguanidine; 3-jodobenzylguanidin; Silver; Iodine; poréznost; povrchové vlastnosti; radiofarmaka; Metal Nanoparticles; Methylmethacrylates; Iodide; Porosity; Silver nanoparticles; methylmetakryláty; Monoliths; Radiopharmaceuticals; Surface Properties; stříbro; Capture